2013
DOI: 10.1007/s13278-013-0135-7
|View full text |Cite
|
Sign up to set email alerts
|

A scalable heuristic for viral marketing under the tipping model

Abstract: In a "tipping" model, each node in a social network, representing an individual, adopts a property or behavior if a certain number of his incoming neighbors currently exhibit the same. In viral marketing, a key problem is to select an initial "seed" set from the network such that the entire network adopts any behavior given to the seed. Here we introduce a method for quickly finding seed sets that scales to very large networks. Our approach finds a set of nodes that guarantees spreading to the entire network u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
38
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(38 citation statements)
references
References 29 publications
0
38
0
Order By: Relevance
“…Various techniques based on centrality measures [4] and more recently the tipping model [7] exist. Irrespective of the method, traditional approaches consider static graphs or periodic snapshots on which they run the entire algorithm and recompute the set from scratch.…”
Section: B Incremental Graph Analytics Algorithms For Identifying Kementioning
confidence: 99%
See 3 more Smart Citations
“…Various techniques based on centrality measures [4] and more recently the tipping model [7] exist. Irrespective of the method, traditional approaches consider static graphs or periodic snapshots on which they run the entire algorithm and recompute the set from scratch.…”
Section: B Incremental Graph Analytics Algorithms For Identifying Kementioning
confidence: 99%
“…We rely on a recently proposed algorithm based on shell decomposition [7] as it was demonstrated to outperform the classic centrality measures and show robustness against the removal of high-degree nodes. This algorithm allows us to determine the smallest possible set of individuals (seed set) such that, if initially activated, the entire population will eventually become activated, adopting the new property, or in our case re-tweeting the ad.…”
Section: B Incremental Graph Analytics Algorithms For Identifying Kementioning
confidence: 99%
See 2 more Smart Citations
“…However, recent investigations have shown that the micro-processes involved in social contagion are complex [13][14][15][16]. A family of models take into account social peculiarities by assuming a discontinuous response of a node to the inflow information [17]. These models are inspired in the classical threshold model [18] where the adoption of an initiative depends basically on whether a minimum number of neighbors have already adopted it.…”
Section: Introductionmentioning
confidence: 99%